THEORETICAL POWER CHARACTERISTICS OF THE SECONDARY WIND TURBINE OF A WIND POWER PLANT WITH AERODYNAMIC MULTIPLICATION - Alekseevskiy , D.; Manaiev , K.; Стрункін , Г. М. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2025)
For the engineering calculation of a wind power plant with aerodynamic multiplication, a power characteristic of its secondary wind turbine is required. The existing model of a wind power plant with aerodynamic multiplication is complex and re-quires a large number of calculations. The purpose of the work is to calculate the power characteristics of a secondary wind turbine and develop a simpler analytical model that will allow for both engineering calculations and further optimization and search for the maximum power equation. Method. An approximation of the characteristic has been developed that replaces a large number of calculations when calculating the power of a secondary wind turbine. Scientific novelty. Based on the existing causal model, a regression model was developed, which allowed us to form a new scientific position on the maximum power of the secondary wind turbine of a wind power plant with aerodynamic multiplication and to identify the zone of available autooptimization. Practical significance. An engineering methodology for calculating the power characteristics of a secondary wind tur-bine of a wind power plant with aerodynamic multiplication and the line of its maximum power is proposed. References 18, figures 6.